Spectrophomeric Determination of Bismuth with Potassiuum Propyl Xanthante in Water - Naidu, U.V.; Murthy, K.V.S.; Naidu, G.R.K. (Asian Journal of Chemistry, 2010)
A spectrophotometric method for the determination of bismuth in water with potassium propyl xanthate is described. Bismuth in water is complexed with potassium propyl xanthate and the complex is extracted into carbon tetrachloride. The absorbance of the complex is maximum at 300 nm. The molar absorptivity of the complex is 2.92×103l.mol–1 cm–1 and it obeys Beer's Law in the concentration range of 2 to 60 μg of bismuth in 10 ml of the sample.